The Impending Population Decline in Northern Norway: Implications and Demographic Challenges - Øyvind Vennerød; Karl Eirik Schjøtt-Pedersen (Arctic Review on Law and Politics, 2023)
This study presents an analysis of population trends in rural Norway, with a specific focus on the potential implications for rural populations in a long-term perspective. We highlight the significant outward migration of young people from rural areas, which has led to a demographic shift happening at a faster pace and on a larger scale in rural areas compared to central areas. Using North-Varanger, the most north-eastern part of the country, as an example, the article shows that the region has experienced net outward migration for the past 50 years, and if current trends persist, the population in the region could decrease by up to 80 percent by 2100. North-Varanger is an area of strategic importance to Norway. It is also an area of vital importance for the Sami people. This study shows that there is a risk that the population in one of the most strategically important regions will see a dramatic reduction. The only way to reverse this trend is to change the migration patterns and encourage more young families to settle in North-Varanger. This stresses the urgent need for policymakers to re-evaluate current public measures aimed at attracting migrants to rural areas in order to make the measures more effective and to ensure sustainable settlement in the region.